Agentes polinizadores e produção de grãos em cultura de café arábica cv. “Catuaí Vermelho” - Malerbo-Souza, Darclet Teresinha; Halak, Andre Luis (My University, 2012)
Coffee (Coffea arabica L.) plants had the pollination process of their flowers studied in three coffee producing regions in Brazil: the first in Ribeirao Preto, state of São Paulo, in September of 2004, the second in Carmo do Paraiba, in the state of Minas Gerais, in October of 2006, and, the third, in Altinopolis, state of São Paulo, in September of 2007. In all these locations the coffee variety used was the 'Catuai Vermelho'. The pollinator species visiting the flowers, the frequency with which the flowers were visited by the insects, and the type of material collected by them ( nectar and/or pollen) were determined by counts taking place at the first 10 minutes of each hour from 7:00 AM till 6:00 PM during the months mentioned above. To estimate the fructification percentage, 25 branches were identified with color threads and protected with wire frames covered with a nylon fabric to prevent them from being visited by insects. Another group of 25 branches was similarly identified but remained without any covering so that their flowers were thus freely visited by insects. on the average, the most frequent pollinator was the Africanized bee Apis mellifera (73.7%) followed by the bee Trigona spinipes (14.5%), and Tetragonisca angustula (9.5%). The Africanized bee collected nectar and pollen to almost the same extent: 58.5% of the first and 41.5% of the second. To collect nectar, that species increased its visiting frequency up to 1:00 PM. To collect pollen, A. mellifera visited the flowers up to 1:00 PM with frequency peaks between 8:00 and 9:00 AM. T. spinipes collected pollen (58,5%) and nectar (41.5%). T. angustula collected only pollen. The branches freely visited by insects produced 181 grains on the average whereas those covered with the nylon fabric produced only 81 grains, this meaning a reduction of 55.25% in grain production. Coffee grains produced on the freely visited branches had a mean weight (1.13 g) significantly superior to that of those produced on the covered branches (0.94 g).
Pollinators and grain production in Arabica coffee crop cv. "Catuai Vermelho".